(NsOBRANIE SO^INENIJ W DEWQTI TOMAH(B;s (NkOLA bR@NXON(B: [(NrOMAN(B] /s (N~ASTX (B5s - (NrOLLAN(B, (NrOMENs ((NmOSKWA(B: s (NpRAWDA(B, s, 1983)
(Nw PQTYJ TOM WO[LI ROMANY(B: "(NkOLA bR@NXON(B", "(NlIL@LI(B", "(NpXER I l@S(B".s
(NlIL@LI(B, (NpXER I l@Ss
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NrOMANs